PRECARIAT AS A SOCIO – POLITICAL PHENOMENON: IN WHAT ARE THREATS? - Зархіна, М. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article discusses the concept of precariat, its content as a socio-economic and politicalphenomenon, explains the reasons for its emergence, the main characteristics, countries’ features.The causes and consequences of the existence and functioning of precariat are elucidated in differentcountries of the world and in Ukraine, particularly. Emerging threats are detected in the process ofprecarization and the risks associated with it.